Analysis of the sectorial policies of China, to understand its model of development - Amado Asenjo, Camilo (2022)
In the last few years, the importance of China for our country (Peru) has been evident and necessary, especially during the COVID-19’s pandemic. In that sense, in the following article, we will seek to understand the development model of that country, in the conceptual framework of the new growth theory and the theory of coordination failure. To achieve that, we will follow the mixed methodology of Cabrejo Villagarcía: to seek the manifestation of the model of development of a country on its sectorial policies (movement of capitals, globalization and technology, deindustrialization, creation of jobs, infrastructure, and productive spending of the State); on the base of the data from primary sources (the Office of National Statistics of China) and from secondary sources (the World Bank, for example). About it, we found that the sources could have ideological and political bias, and that the methodology of analysis doesn’t take into account important things such as culture and cosmovision; nevertheless, on bases of those data, we can conclude that the Chinese development manifested in the following way: industrialization of products with added value, exports of their own industrial products, technology based on national investment, service employment, partial equity, movement of people and information, and state expending from and for the local.